Pedagogical Ideas of Anatolii Pohribnyi in the System of National Education Forming - Matsko, Vitalii (Pedagogical Discourse, 2015)
In the proposed article for the first time national pedagogical ideas of A.H.Pohribnyi, as humanistic ones, have been shown. In his practice, he recognized the value of a person as an individual’s right to freedom, happiness, development and manifestation of his or her talent, considered the principles of equality, justice, humanity as desirable norm of relationships between people. Promoting national idea, humane values ​​in Ukrainian pedagogy he guided the basic principles of love for others, respect for human dignity. A.Pohribnyi understood that Ukraine’s accession to European and Euro-Atlantic structures will require understanding of the own identity, inclusion of the system of national and state priorities, which are designed to achieve the beautiful Ukrainian perspective. And it is the latter, which is grounded on millennial historic-cultural, educational tradition.